PENERIMAAN PENGUKURAN PEMETAAN TANAH DAN PENERIMAAN PEMERIKSAAN TANAH SEBAGAI SUMBER PENDAPATAN (STUDY KASUS DI KANTOR PERTANAHAN KABUPATEN BLORA) - Ova Nur Azizah (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2020)
The purpose of this research is to determine the Income Potential of Land Mapping Measurement and Land Inspection as a source of income Non-Tax State Revenue (PNBP) in the Blora Land Office that is missing and to find the factors causing the loss. The type of data used is secondary data obtained indirectly from the source, namely Realization of Land Mapping Measurement and Land Inspection for the 2014-2018 period at the Blora Land Office and registered parcels obtained from the Financial and Asset Management Revenue Agency Regions (BPPKAD) of Blora. The source of income is still high but cannot be utilized optimally because the percentage of average effectiveness per year for Receiving Land Mapping Measurement is 79.87 percent and Land Inspection Receiving is 62.08 percent, which is marked by the high Expected Opportunity Loss (EOL) Mapping Measurement Land by 83.93 percent and Land Inspection by 83.21 percent. Factors that influence the loss of revenue Land Mapping Measurement and Land Inspection are largely influenced by social and economic factors of the community in Blora Regency.